Histone H3 Acetylation is Asymmetrically Induced Upon Learning in Identified Neurons of the Food Aversion Network in the Mollusk Helix Lucorum - Danilova, Alexandra В.; Kharchenko, Olga; Shevchenko, Konstantin G.; Grinkevch, Larisa N. (Frontiers in Behavioral Neuroscience, 2010)
Regulation of gene expression is an essential step during long-term memory formation. Recently, the involvement of DNA-binding transcription factors and chromatin remodeling in synaptic plasticity have been intensively studied. The process of learning was shown to be associated with chromatin remodeling through histone modifications such as acetylation and phosphorylation. We have previously shown that the MAPK/ERK (mitogen-activated protein kinase/extracellular signal-regulated kinase) regulatory cascade plays a key role in the food aversion conditioning in the mollusk Helix. Specifically, command neurons of withdrawal behavior exhibit a learning-dependent asymmetry (left-right) in MAPK/ERK activation. Here, we expanded our molecular studies by focusing on a potential MAPК/ERK target - histone H3. We studied whether there is a learning-induced MAPK/ERK-dependent acetylation of histone H3 in command neurons RPa(2/3) and LPa(2/3) of the right and left parietal ganglia and whether it is asymmetrical. We found a significant learning-dependent increase in histone H3 acetylation in RPa(2/3) neurons but not in LPa(2/3) neurons. Such an increase in right command neurons depended on MAPK/ERK activation and correlated with a lateralized avoidance movement to the right visible 48h after training. The molecular changes found in a selective set of neurons could thus represent a lateralized memory process, which may lead to consistent turning in one direction when avoiding a food that has been paired with an aversive stimulus.